Regional analysis assessment of landslide hazard and zoning map for transmission line route selection using GIS - Baharuddin I.N.Z.; Omar R.C.; Usman F.; Mejan M.A.; Halim M.K.A.; Zainol M.A.; Zulkarnain M.S. (Institute of Physics Publishing, 2023)
The stability of ground as foundation for infrastructure development is always associated with geology and geomorphology aspects. Failure to carefully analyze these aspects may induce ground instability such subsidence and landslide which eventually can cause catastrophe to the infrastructure i.e. instability of transmission tower. However, in some cases such as the study area this is unavoidable. A GIS system for analysis of route was favoured to perform optimal route predictions based selection by incorporating multiple influence factors into its analysis by incorporating the Landslide Hazard Map (LHM) that was produced on basis of slope map, aspect map, land use map and geological map with the help of ArcGIS using weighted overlay method. Based on LHM it is safe to conclude that the proposed route for Ulu Jelai- Neggiri-Lebir-LILO transmission line has very low risk in term of landslides. Published under licence by IOP Publishing Ltd.